Psicoterapia e formação em psicologia: uma análise da perspectiva de estagiários em psicologia clínica da UFMA - SOUSA JÚNIOR, Josman Raimundo de (2021)
The implications for acting in clinical practice in Psychology demand, besides the skills of the psychologist, personal aspects that become relevant, especially when dealing with a beginning psychotherapist. Considering that the training of a professional occurs throughout graduation and his/her approach to professional practice occurs more directly when students are faced with supervised internships, the present research chose as participants Psychology students from the Federal University of Maranhão who could speak of their experiences in the supervised internship in Clinical Psychology. Thus, this study is defined as exploratory and descriptive and its main purpose is to investigate the place of psychotherapy and its relationship with training and clinical practice in Psychology, from the perspective of interns in the clinical area of Psychology course at the Federal University Maranhão (UFMA). As specific objectives, it intends to investigate psychotherapy as a tool for training in Psychology and describe the relationship between psychotherapy as a personal process for students and its influence on professional performance in the clinical area. To achieve these objectives, the interview technique and a semi-structured script were used, analyzed by the phenomenological method developed by Amadeo Giorgi. As a basis, it was used studies on the history of Psychology in Brazil as a science and profession, on clinical practice and psychotherapy, in addition to documents and regulatory standards of teaching in Psychology. Among the phenomena found, there are 4 (four) units of meaning found from the interviewees' experiences reported in the interviews, which signal relevant aspects in the relationship between psychotherapy, training and internship in the clinical area, they are: internship experience, professional help, self-knowledge, accessibility and personal issues. From these units of meaning, it was possible to conclude that students perceive psychotherapy and the internship experience as a crucial moment in their training, as well as the importance of experiencing psychotherapy as a process of self-knowledge beneficial to their lives, despite presenting obstacles to access and engagement in the psychotherapeutic process. This research is expected to collaborate with other studies and reflections on this topic.